Fintrac - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Fintrac implements agribusiness programmes in Africa, the Caribbean, Central America and Asia, focusing on market-led production, post-harvest and processing assistance to commercial enterprises in the agricultural sector.